2017
DOI: 10.1007/s10258-017-0136-y
|View full text |Cite
|
Sign up to set email alerts
|

Exchange rate volatility and capital inflows: role of financial development

Abstract: There is vast literature examining the impact of exchange rate volatility on various macroeconomic aggregates such as economic growth, trade flows, domestic investment, and more recently capital flows. However, these studies have ignored the role of financial development while examining the impact of exchange rate volatility on capital flows. This study aims to analyze the impact of exchange rate volatility on capital inflows towards developing countries by incorporating the role of financial development over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 41 publications
1
7
0
1
Order By: Relevance
“…In any case, the financial development should assist in reducing the negative effects of the exchange rate volatility on capital inflow, which leads to a conclusion that a developed financial system is a significant channel through which less developed countries can improve capital inflow in the long term. This is especially related to mechanization of remittances that financial sector development should ensure (Jehan & Hamid, 2017).…”
Section: Overview Of Previous Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…In any case, the financial development should assist in reducing the negative effects of the exchange rate volatility on capital inflow, which leads to a conclusion that a developed financial system is a significant channel through which less developed countries can improve capital inflow in the long term. This is especially related to mechanization of remittances that financial sector development should ensure (Jehan & Hamid, 2017).…”
Section: Overview Of Previous Researchmentioning
confidence: 99%
“…1 (2021), pp. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] of its existence as well as the elements and conditions that cause it. The nature of the relationship stems from the fact that a well-functioning financial system facilitates the diversification of risks and effective allocation of capital, and that the financial market development promotes the mobilization of savings and their allocation towards high-efficiency projects (Kutan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Tetapi dampak tidak langsung volatilitas nilai tukar yang terjadi karena perkembangan finansial justru positif. Hal ini menunjukkan bahwa perkembangan finansial mengurangi dampak buruk dari ketidakstabilan nilai tukar terhadap arus modal masuk (Jehan dan Hamid, 2017). Perkembangan finansial ini juga penting dalam menghadapi aliran dana asing yang masuk.…”
Section: Tinjauan Teoretisunclassified
“…They concluded that FDI was negatively influenced by volatility in exchange rate but price volatility has shown no significant impact on foreign direct investment. Jehan and Hamid (2017) have probed the impact of exchange rate volatility on financial and physical capital inflow for a panel of developing economies incorporating the impact of financial development. They concluded that exchange rate volatility adversely affects both kinds of capital inflows however; financial development can mitigate this negative impact.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some of the studies has measured capital inflows by foreign portfolio investment (Rashid & Husain, 2013;Udoh & Egwaikhide, 2008). Jehan and Hamid (2017) have measured the capital inflows by FDI as well as remittances inflow.…”
mentioning
confidence: 99%